The mental health status of asylum seekers in middle- to high-income countries: a synthesis of current global evidence. Issue 1 (14th May 2020) - Posselt, Miriam; McIntyre, Heather; Ngcanga, Mtho; Lines, Thomas; Procter, Nicholas
Abstract: Introduction: The last 5 years have witnessed a significant increase in the number of people fleeing their countries of origin and seeking refuge in host countries. By the end of 2018, there were 3.5 million asylum seekers awaiting outcomes on their applications, the majority of whom were hosted by middle- to high-income countries. This review aimed to identify and synthesize current knowledge regarding the mental health status of asylum seekers in middle- to high-income countries. Sources of data: A search was conducted across various databases for research literature published within the last 5 years (2014–2019). The final review and synthesis included 25 articles. Areas of agreement: Findings highlighted significant differences in the mental health status of asylum seekers compared to those with refugee status and permanent residence. Areas of controversy: Guidelines from the World Health Organization and the United Nations High Commissioner for Refugees emphasize the need to understand and address mental health issues. Instead, there have been policy changes in many host countries regarding asylum applications, and the associated effects of these changes have been shown to negatively impact mental health. Growing points: The synthesized findings from the present review provide information regarding the current mental health status of asylum seekers hosted by middle- to high-income countries. Areas of intervention and resource allocation were also identified. Areas timely for developing research: Future research should consider the impact of large-scale, low-cost interventions to support the mental health of those seeking asylum.